2015
DOI: 10.1088/1475-7516/2015/09/027
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the flux distribution function of the extragalactic gamma-ray background from dark matter annihilation

Abstract: Abstract. The one-point function (i.e., the isotropic flux distribution) is a complementary method to (anisotropic) two-point correlations in searches for a gamma-ray dark matter annihilation signature. Using analytical models of structure formation and dark matter halo properties, we compute the gamma-ray flux distribution due to annihilations in extragalactic dark matter halos, as it would be observed by the Fermi Large Area Telescope. Combining the central limit theorem and Monte Carlo sampling, we show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…Note that many of the details presented in this section have appeared in the earlier works of (Malyshev & Hogg 2011;Lee et al 2015Lee et al , 2016), however we have reproduced these here in order to have a single clear picture of the method.…”
Section: Appendix a Mathematical Foundations Of Nptfitmentioning
confidence: 96%
See 2 more Smart Citations
“…Note that many of the details presented in this section have appeared in the earlier works of (Malyshev & Hogg 2011;Lee et al 2015Lee et al , 2016), however we have reproduced these here in order to have a single clear picture of the method.…”
Section: Appendix a Mathematical Foundations Of Nptfitmentioning
confidence: 96%
“…This section reviews the NPTF, which was first presented in Lee et al (2016) and is described in more detail in Linden et al (2016) and Lisanti et al (2016) (see also Malyshev & Hogg 2011;Lee et al 2015;Zechlin et al 2016aZechlin et al , 2016b. The NPTF is used to fit a model  with parameters q to a data set d consisting of counts n p in each pixel p. The likelihood function for the NPTF is then simply…”
Section: The Non-poissonian Template Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…Different populations of gamma-ray emitters induce anisotropies in the UGRB with different amplitudes and different angular and energy spectra [2]. A measurement of the gamma-ray angular power spectrum (APS) can therefore constrain the nature of the UGRB in a complementary way with respect to the intensity energy spectrum and the 1-point photon count probability distribution [3][4][5][6][7][8]. A different but related approach based on two-point statistics is the cross correlation of the gamma-ray sky with independent probes tracing the large scale structures of the Universe [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty years later, the calculation was revisited [7,8] based on an improved understanding of structure formation in the ΛCDM cosmological paradigm: contrarily to previous estimates, the DGRB was found to be a promising entity to probe for signatures of DM annihilation. Many efforts followed to refine this calculation (see [1] for a comprehensive list of references), or to go beyond the simple average calculation to increase the sensitivity to the DM signal against astrophysical backgrounds (via the photon distribution function [9], searching for a small-scale anisotropy in the DGRB via auto-correlations [10] or cross-correlations with galaxy catalogues [11]). Based on these calculations and the analysis of four years of Fermi-LAT data [12,13], several authors [13][14][15][16] recently concluded that the limits on dark matter candidates derived from the DGRB are competitive with the best constraints on DM set by dwarf spheroidal galaxies [17,18], and that they are currently the best limits set by Fermi-LAT data at TeV masses.…”
Section: Introductionmentioning
confidence: 99%